Pharmacokinetic and Pharmacodynamic Properties of Batifiban Coadministered with Antithrombin Agents in Chinese Healthy Volunteers - 何晓梦 周莹 李杰 伍三兰 贾萌萌 刘明周 谌辉 谌科 李圣峰 王耀华 黎维勇 (Journal of Huazhong University of Science and Technology. Medical sciences, 2013)
The combined use of batifiban, a synthetic platelet GP II b/IIIa receptor antagonist, and an- tithrombin agents is an attractive option for the treatment of patients with non-ST-segment elevation （NSTE） acute coronary syndrome （ACS） and those scheduled for percutaneous coronary intervention. To observe whether antithrombin agents affect the pharmacokinetic and pharmacodynamic properties of batifiban in combination therapy and optimize clinical administration dosage of batifiban, an open-label and parallel study was conducted. Thirty healthy subjects were randomly divided into three groups, which were sequentially treated with batifiban alone, or oral coadministration of clopidogrel, aspirin and UFH, or batifiban coadministered with these antithrombin agents. Blood samples were collected at pre-specified time points. The evaluation index included the inhibition of platelet aggregation and pharmacokinetic parameters. The pharmacokinetic parameters of batifiban and batifiban coadministered with antithrombin agents showed no significant differences. The mean inhibition rate of platelet aggre- gation （%） suggested that neither batifiban alone nor antithrombin agents alone could provide such po- tent inhibition rate （〉80%） to obtain the best clinical efficacy, but they had a synergistic effect on plate- let inhibition. No serious adverse effects were observed. The results in these healthy subjects suggest that batifiban coadministrated with antithrombin agents could achieve optimum clinical treatment effect for patients with NSTE ACS, and also those scheduled for percutaneous coronary intervention.